Ketidaklangsungan Ekspresi Dalam Lirik Lagu Album Manusia Karya Tulus Dan Implikasi Pada Pembelajaran Sastra di SMP - Betiana Betiana; Patrisia Cuesdeyeni; Yuliati Eka Asi; Alifiah Nurachmana; Jumadi Jumadi (Universitas Palan, 2023)
This research approach is descriptive qualitative, which is in line with the research findings, namely in the form of a description of the Indirectness of Expression in the Song Lyrics of the Album Human Karya Tulus. This type of research is qualitative, because the data found were not obtained using statistical (quantitative) calculations but in the form of phrases, clauses or sentences contained in indirect expressions in the lyrics of the song Album Human Karya Tulus. The results of this research show that the analysis of deviations in meaning and creation of meaning in the lyrics of the song Album Human Karya Tulus obtained data that the indirectness of expression in the song lyrics in the form of replacement of meaning in the form of metaphor amounted to eight quotations, personification amounted to eleven quotations, deviations in meaning in the form of ambiguity amounted to six quotations , contradiction of three quotations, creation of meaning in the form of rhyme totaling six quotations and creation of meaning in the form of typography totaling three quotations. Thus, the indirect expression in the song lyrics that is most dominantly used in the Human Album by Tulus is the indirect expression in the song lyrics in the form of changing meaning in the form of personification totaling eleven quotes. The implications of the analysis of indirectness of expression in the lyrics of the song Album Human Karya Tulus for literature learning in junior high schools are expected to provide an understanding of the types of indirectness of expression in a song lyric. These implications are also expected to become additional teaching material to improve students' abilities in understanding the building blocks in a song lyric as well as creating a work of song lyrics.